Autoantibodies against C-Reactive Protein Influence Complement Activation and Clinical Course in Lupus Nephritis - Li, Qiu-yu (J Am Soc Nephrol, 2017)
Autoantibodies against the major acute-phase reactant C-reactive protein (CRP) are frequently found in patients with lupus nephritis. Further defining the autoimmune epitopes on CRP may not only improve patient stratification but also, hint at mechanisms of CRP action. Herein, we show that amino acids 35–47 constitute the major epitope recognized by anti-CRP autoantibodies in patients with lupus nephritis. Notably, the presence of autoantibodies against amino acids 35–47 associated with more severe renal damage and predicted worse outcome. This epitope is exposed on CRP only after irreversible structure changes, yielding a conformationally altered form termed modified or monomeric CRP (mCRP). ELISA and surface plasmon resonance assays showed that amino acids 35–47 mediate the interaction of mCRP with complement factor H, an inhibitor of alternative pathway activation, and this interaction greatly enhanced the in vitro cofactor activity of complement factor H. In contrast, autoantibodies against amino acids 35–47 inhibited these actions of mCRP. Our results thus provide evidence for the in vivo generation of mCRP in a human disease and suggest that mCRP actively controls the pathogenesis of lupus nephritis by regulating complement activation. Therefore, amino acids 35–47 constitute a functional autoimmune epitope on CRP that can be targeted therapeutically and diagnostically.